M.HRUSHEVSKY’S PUBLICATIONS FOR PEASANTS IN HISTORIOGRAPHICAL PERCEPTION AT THE BEGINNING OF XX CENTURY - V. Telvak; О. Vladyga (Український селянин, 2019)
The article is devoted to the research of perception of scientific-popular works of M. Hrushevsky. It highlights the need for such works among peasants. The article demonstrates that reviewers recognized Hrushevsky as a forerunner of educating peasants on the Ukrainian past in context of Ukrainian historical process.